(untitled) (Journal of Educational Sciences, 2022)
The problem of the psych emotional state of students in the learning process is of great practical importance in the context of studying the emotional stability of the personality. The introduction of distance learning, innovative computer technologies in educational practice cannot but affect the psych emotional state of students. The mental and physical health of a student is directly related to the emotional security of the educational environment. During the period of isolation, the student is influenced by a complex of factors: the family environment, increased social and emotional stress, an increase in educational and computer load, an increase in responsibility for doing homework, which affects the behavioral sphere. In order to study the peculiarities of the psych emotional state of the study, participated 116 students of the school № 42 of Almaty city were surveyed by the method of questioning during the distance and traditional formats of education, as well as with a self-assessment of the state of health. The results of the study expand the scientific understanding of the psych emotional states of students, contribute to the improvement of methods for their regulation, can be used to develop programs for psychoprophylaxis, psych correction and psychological and pedagogical support of schoolchildren who are forced to be in self-isolation in connection with the transition to distance learning. Key words: educational environment, psychoemotional state, psychophysiology, adaptation, schoolchildren.